A Descriptive Study On Teaching Speaking To The Seventh Year Student Of RSBI Class Of SMP N 1 Lasem, Rembang In 2011/2012 Academic Year - Qoimah, Lailatul (2012)
This research aims at describing teaching speaking to the seventh year students of SMP N 1 Lasem, Rembang in 2011/2012 academic year. The objectives of this research paper are to describe: 1) process of teaching speaking on the seventh year of SMP N 1 Lasem, Rembang, 2) the problems faced by the teacher, 3) problem solving used by the teacher. The type of this research is descriptive qualitative. The data of this research are collected by observing the English class and interviewing the English teacher. The data of this research are the seventh year student's activities in speaking in SMP N 1 Lasem, Rembang in 2011/2012 academic year, field note and data from interviewing English teacher. The subject of this research is English teacher and the seventh grade students of SMP N 1 Lasem, Rembang. The object of this research is teaching speaking to the seventh year students in SMP N 1 Lasem, Rembang. The methods of collecting the data of the research are observation, interview, and documents. Based on the result of the analy sis, the teacher uses BKOF, MOT, JCOT, ICOT as the learning procedure. The objective of teaching speaking is developing and preparing the student's speaking skill. The materials are students worksheet and real situation. The media are picture, realia, and LCD projector. The techniques are role playing, modeling, pair work and discussion, practice and assessment, game, conversations practice, and repetition and translation. The evaluation is conducted by interpreting all of English skills. While the teacher roles are facilitator, councelor, and motivator. The teacher's problems are a) the influence of Javanese in the student's ability, b) the different competence of the students, c) the student's self confidence. To solve the problem a) the teacher used English in learning process, b) the teacher repeated the material and gave example to reinforce their understanding, c) the teacher involved all of the students to support their friend by giving applause and applying pair work discussion to minimize their anxiety.